2022
DOI: 10.1111/jch.14449
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between non‐insulin‐based insulin resistance indexes and the risk of prehypertension: A cross‐sectional study

Abstract: The authors aimed to characterize the relationships between non‐insulin‐based insulin resistance (IR) indexes and the risk of prehypertension, and to compare their abilities to identify prehypertension. The authors recruited 3274 adults who did not have hypertension and were not taking hypoglycemic or lipid‐lowering medications. The triglyceride‐to‐high‐density lipoprotein‐cholesterol ratio (TG/HDL‐C), fasting triglyceride and glucose index (TyG), and metabolic score for IR (METS‐IR) were calculated. Bivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Therefore, a number of simple, inexpensive and reproducible alternative parameters have emerged, which have been shown to replace HEC for IR. These parameters include the ratios of triglycerides and specific components of cholesterol, TyG and TyG-related parameters, metabolic score for insulin resistance (METS-IR), visceral adiposity index (VAI) and lipid accumulation product (LAP), whose association with IR has been explored ( 16 , 30 , 31 ) and compared in the prediction of some specific diseases ( 32 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a number of simple, inexpensive and reproducible alternative parameters have emerged, which have been shown to replace HEC for IR. These parameters include the ratios of triglycerides and specific components of cholesterol, TyG and TyG-related parameters, metabolic score for insulin resistance (METS-IR), visceral adiposity index (VAI) and lipid accumulation product (LAP), whose association with IR has been explored ( 16 , 30 , 31 ) and compared in the prediction of some specific diseases ( 32 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have found that METS-IR has a better predictive value for ischemic heart disease 35 and prehypertension or hypertension among normoglycemic participants. 36,37 This could help to analyze the association between METS-IR and other metabolic diseases.…”
mentioning
confidence: 99%
“…The index shows a strong correlation with the IR measured by the hyperinsulinemic-euglycemic clamp technique and is associated with fasting insulin, and accumulation of intrahepatic, intravisceral, and subcutaneous fat, which is a key mechanism in the development of IR 9 . The positive correlation between the METS-IR index and metabolism-related or inflammationrelated diseases, including diabetes 9 , metabolic syndrome 10 , hypertension 11,12 , and nonalcoholic fatty liver disease 13 has been found by previous research, each of which are recognized as significant risk factors for developing CVD. Several studies have shown the association of HOMA-IR or TyG-related indices with arterial stiffness 14,15 and CVD 16,17 .…”
Section: Introductionmentioning
confidence: 66%
“…They found that the use of the METS‐IR index was effective in predicting hypertension and arterial stiffness 33 . Recently, several studies have also shown similar findings 11,12,34–36 and therefore suggested a correlation between the METS‐IR index and CVD, as arterial stiffness and hypertension are the pathological basis and independent risk factors for CVD 37 , respectively. In our study, compared with the lowest quartile of METS‐IR, participants in the other groups had higher levels of FPG, 2 h PG, HbA1c, BMI, TG, TC, and LDL, and lower levels of HDL and eGFR.…”
Section: Discussionmentioning
confidence: 84%